Higher education in the paradigm of speed: Student perspectives on the risks of fast-track degree completion. Issue 1 (1st March 2020) - Sarauw, Laura Louise; Madsen, Simon Ryberg
Abstract: Studies often highlight how standardisation and consent are manufactured through the European Bologna Process (Brøgger 2019 ; Gibbs et al. 2014 ; Lawn and Grek 2012 ). This article shows how students' conduct is still governed by multiple logics and dilemmas. The context for the article is the Bologna Process and the way it has been applied by the Danish government in the 2014 reforms that sought to fast-track the completion of student degrees. It analyses the impact of changes on students' conduct through a series of focus group interviews with students who were confronted with the new demands to speed up their progress through their degrees. To illustrate the complexity of this standardisation, the analyses are framed within theoretical ideas of 'risk' (Beck 2006 ) and 'translation' (Latour and Callon 1986 ).